Identifying Peer Effects in Student Academic Achievement by Spatial Autoregressive Models with Group Unobservables - Lin, Xu (Journal of Labor Economics, 2010)
Disentangling peer effects from other confounding effects is difficult,and separately identifying endogenous and contextual effects is impossible for the linear-in-means model. This study confronts these problems by using spatial autoregressive models with group fixed effects. The nonlinearity introduced by the variations in the peer measurements provides information to identify both endogenous and contextual effects,thus resolving the "reflection problem." The group fixed effects term captures the confounding effects of the common variables.Applying the model to data sets from the National Longitudinal Studyof Adolescent Health, I find strong evidence for both endogenous and contextual effects in student academic achievement. (c) 2010 by The University of Chicago. Allrights reserved.